DAMPAK PEMBELAJARAN MATEMATIKA SETELAH PANDEMI TERHADAP MOTIVASI BELAJAR SISWA SMPN 1 BUKITTINGGI - Manja Ayu Sasmita; M. Imamuddin; Citra Fahdilla; Neldawati Neldawati (Universitas Pahlawan Tuanku Tambusai, 2022)
The abstract should end with a comment about the importance of the results or a brief conclusion. This study aims to find out about the impact of learning mathematics after the pandemic on students' learning motivation at SMPN 1 Bukittinggi. In this study, researchers used a type of qualitative research. The samples in this study were 58 students in class VII E and VII F, consisting of 27 students in class VII E and 31 students from class VII F. Data collection techniques used in this study were observation, documentation, and questionnaires. . The results show that the learning motivation of SMPPN 1 Bukittinggi students is in the good category with an average percentage of 77%, consisting of five indicators namely persistence in learning that 58 respondents or 87%. Tenacious in facing difficulties as many as 58 respondents or 89%. Interest and sharpness of attention in learning as many as 58 respondents or 83%. Achievement in learning as many as 58 respondents or 83%. And independent in learning as many as 58 respondents or 72%. Keywords: Mathematics, Pandemic, Learning motivation